3D-printed vancomycin-eluting PGCL/MXene bifunctional scaffold for management of infected bone defects - Xipeng Chen; Yuanpei Cheng; Yongbo Li; Ze Tan; Han Wu (Materials Today Bio)
The clinical management of infected bone defects remains a significant challenge in orthopedic surgery. In this study, we developed a multifunctional composite scaffold by integrating MXene (Ti3C2) nanosheets and vancomycin (Van) into a degradable poly(glycolide-co-caprolactone) (PGCL) polymer through precision 3D printing technology, with the aim of regenerating acutely infected bone defects. Systematic optimization established the optimal composition as 5 wt% Ti3C2 and 5 wt% Van within the degradable PGCL polymer. Compared with PGCL scaffolds, a significantly thicker mineralized layer could be deposited on the PGCL@5 %Ti3C2/5 %Van surface in simulated body fluid (SPF). The in vitro results showed that the PGCL@5 %Ti3C2/5 %Van scaffold had antibacterial properties, cytocompatibility, osteoblast differentiation and extracellular mineralization. The in vivo results showed that the PGCL@5 %Van/5 %Ti3C2 scaffold effectively inhibited infection caused by methicillin-resistant Staphylococcus aureus (MRSA) in bone defects and promoted bone repair. The potential mechanism of Ti3C2 in anti-inflammatory and osteogenic induction was investigated through transcriptome analysis. These results suggest that Ti3C2 is involved in the regulation of the PI3K‒Akt signalling pathway to increase osteogenic induction ability and regulate the inflammatory response by downregulating the NF-κB pathway through the deiodinase iodothyronine type II (DiO2). These findings indicate that the PGCL@5 %Ti3C2/5 %Van scaffold can enhance the regeneration of acutely infected bone defects.